The Influence of Work Discipline, Motivation, Competence, and Work Environment on Work Productivity - Johannes Triestanto; Gurawan Dayona Ismail; Nunung Ayu Sofianti (Efi); Yoyo Sudaryo; Riyandi Nur Sumawidjaja (Eduvest - Journal of Universal Studies, 2026)
Work productivity is one of the most important aspects of an organization. It refers to the results of employees’ work within a certain period, carried out effectively and efficiently by considering the resources used to perform their tasks. This study aims to empirically test and analyze the influence of work discipline, motivation, competence, and work environment on work productivity, both partially and simultaneously. The method used in this study is a quantitative research method with a descriptive and verification approach. The data sources consist of primary and secondary data. Data collection techniques used include interviews, questionnaires, observations, and library research conducted both online and offline. The population in this study includes all 36 employees; therefore, the sampling technique applied is a census sample or total sampling. The analytical tool used is SPSS version 25. The validity and reliability of the data were assessed through validity and reliability tests, classical assumption tests, and data analysis techniques such as multiple linear regression, correlation, and coefficient of determination analyses. Hypothesis testing was conducted using the t-test (partial) and F-test (simultaneous). The results of this study indicate that work discipline, motivation, competence, and work environment have a positive and significant effect on work productivity, both partially and simultaneously, with a contribution of 93.3%, while the remaining 6.7% is influenced by other variables not examined in this study.